Centre‐level variation in speech outcome and interventions, and factors associated with poor speech outcomes in 5‐year‐old children with non‐syndromic unilateral cleft lip and palate: The Cleft Care UK study. Part 4. (June 2017) - Sell, D.; Southby, L.; Wren, Y.; Wills, A. K.; Hall, A.; Mahmoud, O.; Waylen, A.; Sandy, J. R.; Ness, A. R.
Structured Abstract: Objectives: To investigate centre‐level variation in speech intervention and outcome and factors associated with a speech disorder in children in Cleft Care UK (CCUK). Setting and Sample Population: Two hundred and sixty‐eight 5‐year‐old British children with non‐syndromic unilateral cleft lip and palate recruited to CCUK. Materials and Methods: Centre‐based therapists undertook audio‐video recordings. Perceptual analysis was undertaken using the CAPS‐A tool. Speech outcomes were based on structural and articulation scores, and intelligibility/distinctiveness. Between‐centre variation in treatment and outcomes were examined using multilevel models. These models were extended to estimate the association between a range of factors (hearing loss, speech intervention, fistula, secondary speech surgery for velopharyngeal insufficiency, socio‐economic status, gender, and parental happiness with speech) and speech outcomes. Results: There was centre‐level variation in secondary speech surgery, speech intervention, structure and intelligibility outcomes. Children with a history of speech intervention had a lower odds of poor intelligibility/distinctiveness, 0.1 (95% CI: 0.0‐0.4). Parental concern was associated with a higher odds of poor intelligibility/distinctiveness, 13.2 (95% CI: 4.9‐35.1). Poor speech outcomes were associated with a fistula, secondary speech surgery and history of hearing loss. Conclusions: Within the centralized service there is centre‐level variation in secondary speech surgery, intervention and speech outcomes. These findings support the importance of early management of fistulae, effective management of velopharyngeal insufficiency and hearing impairment, and most importantly speech intervention in the preschool years. Parental concern about speech is a good indicator of speech status.